Application of Differentiated Learning to The Polyhedron Material in Visual Form to Understanding Ability Junior High School Students Concept - Astuti, Delvia Eri (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
The ability to understand mathematical concepts plays an important role in students' skills and success in learning mathematics. However, in reality, quite a few students have the stigma that mathematics is difficult and scary. This causes a low ability to understand mathematical concepts due to the application of learning strategies that are not appropriate to the abstract field of mathematics and the diverse characteristics of students. The application of content differentiation learning can be a solution to this problem. Mathematics learning aims to turn abstract reasoning into concrete. Visual media as a tool in the differentiated learning process can help students think concretely, explore various mathematical concepts, encourage students to participate actively, and provide meaningful experiences in the learning process to increase understanding of mathematical concepts. The aim of this research is to analyze the relationship between differentiated learning and students' ability to understand concepts in geometry material on the data side in visual form. This research refers to descriptive research with a qualitative approach with a literature review method through exploration of articles related to the research topic. Then carry out research sourced from trusted literature, namely articles, books and research results from experts to answer how the application of differentiation learning with visual media affects students' ability to understand concepts in Polyhedron Material.